Diagnosis Penyakit Ikan Koi Menggunakan Metode Naive Bayes Classifier - Yudo Juni Hardiko; Nurul Hidayat; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Koi fish (Cyprinus carpio) is a type of freshwater ornamental fish that is widely cultivated because it has an attractive body shape and color. Koi morphology is almost similar to other fish species, koi body covered by two layers of skin, the outer skin (epidermis) and the skin (dermis). Epidermis is useful as a protective skin from the outside environment or as protection such as impact, dirt, and pest. Disease attacks and parasitic infections are a common problem faced by fish farmers. Diseases that often attack koi caused by pathogens in the form of bacteria, fungi, or viruses. The pathogens that live in the body of koi is very harmful because it will indirectly affect the color of koi fish. Koi fish diseases generally have some common symptoms that are almost the same as excessive mucus, punctured wounds or lumps on the body of fish and koi fish so menyediri. With so many diseases that have the same symptoms it makes fish farmers difficult to diagnose diseases in koi fish. Many methods can be used to create an system one of them is by using the method of Naive Bayes Classifier. In this system receive input in the form of data koi fish disease symptoms and the data is then processed using the method of Naive Bayes the results of system output in the form of diagnosis of diseases and treatment of disease outcomes that are diagnosed. Based on the accuracy testing of 20 data yields an accuracy of 90%.